Nina Kaucisvili's contribution to the Studies on Russian Culture and Spirituality - Elda Garetto; Rosanna Casari (Studi Slavistici)
This paper outlines the multifaceted intellectual profile of Nina Kaucisvili (1919–2000), from her cosmopolitan education to the development of her distinguished career as a scholar and professor of Russian literature. Her research and teaching primarily focused on the works of Dostoevskij and Gogol’ from the nineteenth century, and Andrej Belyj from the twentieth, applying the theories of the Russian formalists—particularly those of Jurij Lotman—to the analysis of their writings. A significant phase of her scholarly activity centered on the philosophical and aesthetic works of Pavel Florenskij. Thanks to her exceptional ability to identify innovative research directions and to foster opportunities for scholarly debate with leading international experts, the Slavic Department at the University of Bergamo became a major hub for Russian studies. The international academic community recognized not only her original approach to Russian-Italian cultural relations, but also her efforts to broaden cultural discourse to include twentieth-century Russian spirituality, both within Russia and in emigration.